Sektarianisme dalam Penafsiran Relasi Muslim–Non-Muslim: Analisis Komparatif Tafsir Sunni dan Syiah - Syaiful Arief; Hidayatullah; Muhammad Khoirul Anwar (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This article analyzes sectarianism in the interpretation of Qur’anic verses concerning the relationship between Muslims and non-Muslims by comparing classical and modern exegesis from Sunni and Shia traditions. The study focuses on four thematic groups of verses: religious freedom, interfaith dialogue, political allegiance, and interfaith marriage. Employing Hans-Georg Gadamer’s philosophical hermeneutic framework, it explores how the historical and ideological horizons of the exegetes influence their interpretive outcomes. The findings reveal that classical commentaries, such as those of Ibn Kathir and al-Tha‘barsi, tend to be apologetic and normative, while modern exegeses by Wahbah al-Zuhaili and Muhammad Husain al-Thabathabai exhibit a more humanistic and contextual orientation. Despite their sectarian and methodological differences, both traditions share a common ethical aim—to maintain a balance between faith and humanity. This study underscores the significance of inter-sectarian exegetical dialogue as a means to foster an inclusive and universal understanding of Islam.